Plants and Plant Constituents with Analgesic and Anti-inflammatory Activities: A Systematic Review (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Medicinal plants with potential therapeutic activities are a tremendous resources of prospective drug candidates. NSAIDs, opiates, and other anti-inflammatory & analgesic agents exhibit several unwanted side-effects. Thus, the development of new active compounds with minimum adverse effects necessitates an emergence. This study aims to provide a comprehensive summary of plant species and reported phytoconstituents with analgesic and inti-inflammatory activities. Eighty-seven species from fifty-two plant families with reported constituents and activities have been included in this review. In-depth research in the area of screening novel analgesic and antiinflammatory agents from natural sources followed by the investigation of their pharmacological properties and clinical applications may lead to the generation of new active agents with better therapeutic activity and selectivity in the future.Dhaka Univ. J. Pharm. Sci. 19(2): 207-224, 2020 (December)